Diagnostic and prognostic role of the modern instrumental methods for cardiovascular examination in patients with coronary heart disease - V. P. Lupanov (Кардиоваскулярная терапия и профилактика)
The paper reviews the indications, contraindications, limitations, and strengths of the modern functional methods for coronary heart disease (CHD) diagnostics. As well as the widely used electrocardiography (ECG) based exercise stress tests, the following informative methods are described: myocardial perfusion assessment, stress echocardiography (EchoCG), magnetic resonance imaging and multi-spiral computed tomography of the heart. The sensitivity, specificity, diagnostic order, and prognostic value of these methods are compared to those of coronary angiography in CHD patients.